2002
DOI: 10.1111/j.1349-7006.2002.tb01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Dose‐response Relationship for Carcinogenicity in the Rat Liver with Low Doses of 2‐Amino‐3,8‐dimethylimidazo[4,5‐f]quinoxaline or N‐Nitrosodiethylamine

Abstract: For a long period, it has been generally considered that carcinogens, particularly genotoxic ones, have no threshold in exerting their potential for cancer induction. However, the non-threshold theory can be challenged with regard to assessment of cancer risk to humans. Here we show that a food-derived, genotoxic hepatocarcinogen, 2-amino-3,8-dimethylimidazo[4,5-f ]quinoxaline, forms DNA adducts at low doses, but does not induce glutathione S-transferase placental form (GST-P)-positive foci (considered to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
88
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 22 publications
7
88
2
Order By: Relevance
“…7 Thereby, in our laboratory, the nonthreshold theory for hepatocarcinogenesis of one HCA, 2-amino-3,8-dimethylimidazo [4,5-f]quinoxaline (MeIQx), has been challenged, since in vivo dose-response curves do not show linearity at low-dose levels. 8,9 Moreover, thresholds for chemical carcinogenesis were concluded in a recent article. 10 In practice, the many factors active in vivo, from intake of carcinogens through to lesion development, mean that the processes are highly complicated, so that if the DNA-damaging potency of a carcinogen is low, the linear part of the low dose-cancer incidence curve might be hidden within the background variability, and issues of true threshold and practical threshold have therefore been discussed.…”
mentioning
confidence: 99%
“…7 Thereby, in our laboratory, the nonthreshold theory for hepatocarcinogenesis of one HCA, 2-amino-3,8-dimethylimidazo [4,5-f]quinoxaline (MeIQx), has been challenged, since in vivo dose-response curves do not show linearity at low-dose levels. 8,9 Moreover, thresholds for chemical carcinogenesis were concluded in a recent article. 10 In practice, the many factors active in vivo, from intake of carcinogens through to lesion development, mean that the processes are highly complicated, so that if the DNA-damaging potency of a carcinogen is low, the linear part of the low dose-cancer incidence curve might be hidden within the background variability, and issues of true threshold and practical threshold have therefore been discussed.…”
mentioning
confidence: 99%
“…[8][9][10] Fukushima et al 11) have examined the low-dose carcinogenicity of MeIQx in detail using GST-P-positive foci as end-point lesions and have reported a lack of any linear dose-response relationship, suggesting the existence of a practical threshold. In the colon, aberrant crypt foci (ACF) are considered as a preneoplastic lesion, although not all data support a direct correlation with tumor development.…”
mentioning
confidence: 99%
“…It has been demonstrated that with 16 weeks exposure to MeIQx at doses of 0.001 to 100 ppm in diet, 10 and 100 ppm increased GST-P-positive foci, but there was no difference from the control value at 1 ppm and below in male F344 rats. 11,17) Therefore, we selected the doses of 1, 10 and 100 ppm for use in this study.…”
mentioning
confidence: 99%
“…The mutagenicity of MeIQx in Salmonella typhimurium TA98 and TA100 with S9 mix was reported to be the strongest of all HCAs examined (Sugimura et al, 2004). MeIQx is metabolized in vivo to , which is the most abundant DNA adduct associated with oxidative stress and resulting in specific types of mutation, as well as induction of glutathione S-transferase placental form (GST-P)-positive foci, considered the rat liver preneoplastic lesions, was observed at (≤10 ppm) of MeIQx (Fukushima, 1999;Fukushima et al, 2002Fukushima et al, , 2003. Although the number of GST-P-positive foci at 1 ppm was not different from control, it was increased at 10 ppm, albeit without statistical significance.…”
Section: Introductionmentioning
confidence: 99%